Assistive courseware for hearing impaired learners in Malaysia based on theory of Multiple Intelligences (MI) - Shaffiei, Zatul Amilah; Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Jaafar, Mohd Saifullizam (ExcelingTech Publisher, UK, 2011)
This paper reports a research on Hearing Impaired (HI) learners in Malaysia which focuses on beginner level.This research has been carried out with the intention to solve problem faced by parents of HI children in teaching their children to know the six (6) basic sounds which is known as Ling-6 Sound.The HI learners were assisted by specially-developed electronic-learning application or known as Assistive Courseware (AC) in their teaching and learning process.The AC utilizes the mother tongue language.The objectives of the study include 1) To identify the characteristic of AC for HI learners, 2) To design the storyboard of AC for HI learners, and 3) To design the interface of AC for HI learners based on MI theory.This study adapts the Iterative Triangulation Methodology, and it is integrated with the IntView Methodology.The storyboard of the prototype is outlined next.The findings of this paper highlight the prototype of the AC labelled with certain characteristics representing MI theory which is suitable for HI learners and the result is based on interview with parents.The final part concludes this paper.